Rupture of wet mantle wedge by self-promoting carbonation - Atsushi Okamoto (Nature Portfolio, 2021)
Carbonation of a serpentinized mantle wedge is associated with volume reduction and fluid over-pressurization which drives brittle fracture and seismicity, according to chemical analyses of carbonate veins from the Sanbagawa belt Japan and thermodynamic calculations.